2014
DOI: 10.1103/physrevb.89.064311
|View full text |Cite
|
Sign up to set email alerts
|

Polaron dynamics and decoherence in an interacting two-spin system coupled to an optical-phonon environment

Abstract: We study two anisotropically interacting spins coupled to optical phonons; we restrict our analysis to the regime of strong coupling to the environment, to the antiadiabatic region, and to the subspace with zero value for S z T (the z-component of the total spin). In the case where each spin is coupled to a different phonon bath, we assume that the system and the environment are initially uncorrelated (and form a simply separable state) in the polaronic frame of reference. By analyzing the polaron dynamics thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 34 publications
8
48
0
Order By: Relevance
“…However, it is worth noting that the φ-Λ(1520) interference effect does not account for the 2.1-GeV bump structure in forward differential cross sections for φ photoproduction. This result is consistent with a recent report from CLAS regarding the Λ(1520) effect [10]. The energy dependence of the phase may indicate nontrivial rescattering contributions from other hyperon resonances.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…However, it is worth noting that the φ-Λ(1520) interference effect does not account for the 2.1-GeV bump structure in forward differential cross sections for φ photoproduction. This result is consistent with a recent report from CLAS regarding the Λ(1520) effect [10]. The energy dependence of the phase may indicate nontrivial rescattering contributions from other hyperon resonances.…”
supporting
confidence: 93%
“…However, a bump structure at √ s = 2.1 GeV in forward differential cross sections was first reported by the LEPS collaboration [8]. Despite extensive experimental efforts devoted for the photoproduction of φ mesons near threshold, the nature of the bump structure has not yet been explained in detail [9,10]. Kiswandhi et al [11] suggested that the bump structure is the result of an excitation of missing nucleon resonances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1. This behavior was also observed by CLAS [6,7]. The spin density matrix element obtained by the K + K − decay angular distribution shows about 30% contribution of unnatural-parity exchanges such as π 0 and η in the measured energy region.…”
Section: Coherent φ-Meson Photoproduction From 4 Hesupporting
confidence: 76%
“…Here we restrict ourselves to the nonequilibrium dynamics of an electron coupled to phonons (i.e., the polaron dynamics), which has recently become a widely studied topic [20,[34][35][36][37][38][39][40][41][42][43][44][45]. One-electron problems have MPS with low bond dimensions D, which can easily be simulated on a workstation when the effective local dimension is small (d or d O 10).…”
mentioning
confidence: 99%